﻿Mitreola quanruii (Loganiaceae), a new species from a karst region in Guangxi, China - Renchuan Hu; Xiaowen Liao; Binsheng Luo; Cheng Liu; You Nong; Lei Wu (PhytoKeys, 2023)
Mitreola quanruii , a new species from Guangxi, China, is described and illustrated in this study. It is morphologically similar to M. liuyanii because of the terete stems, creeping and branched at the base, the leaves which are pilose on both surfaces and the bilobed capsules with two erect horns. The new species can be distinguished from M. liuyanii by its taller habit, up to 20–50 cm tall, its linear leaves, 4–18 × 0.3–1 cm with acuminate apex and 8–10 pairs of lateral veins, its narrowly triangular stipules, its linear bracts, ca. 1.0 cm long and glabrous and its glabrous calyx. Mitreola quanruii is temporarily assessed as data deficient (DD) according to IUCN. The habitat of Mitreola quanruii is extremely fragile. Therefore, this species deserves close attention and protection.